GAMBARAN PENGETAHUAN IBU TENTANG IMUNISASI DASAR PADA BAYI USIA 0-9 BULAN DI LINGKUNGAN II KELURAHAN SIMALINGKAR B KEC. MEDAN TUNTUNGAN TAHUN 2019 - Hetty Gustina Simamora (Elisabeth Health Jurnal, 2019)
Immunization is a way to increase a person's immunity to a disease, so that if it is exposed to the disease later it does not become sick. Goals of this study was to determine the description of maternal knowledge about the types of basic immunization, the benefits of basic immunization and the schedule of immunization. Method This research method was a descriptive study. The population was mothers who has babies aged 0-9 months.Sample was 38 people. Sampling used total sampling technique. The Results of this study indicated that of the 38 respondents most knowledgeable about the types of basic immunization with a number of 19 respondents (50%), knowledgeable about the benefits of basic immunization with a total of 21 respondents (55.26%) and knowledgeable about basic immunization schedules with a total of 18 respondents (47.37%). Conclusions for mothers who had toddlers should bring their babies to obtain basic immunizations according to their baby's age regularly and to health workers so that the implementation of programs such as health education on basic immunization is often done so that mothers become familiar, who did not know to know